Targeted worker removal reveals a lack of flexibility in brood transport specialisation with no compensatory gain in efficiency - Sean McGregor; Fazil E. Uslu; Mahmut Selman Sakar; Laurent Keller (Scientific Reports, 2024)
Abstract Division of labour is widely thought to increase the task efficiency of eusocial insects. Workers can switch their task to compensate for sudden changes in demand, providing flexible task allocation. In combination with automated tracking technology, we developed a robotic system to precisely control and spatiotemporally manipulate floor temperature over days, which allowed us to predictably drive brood transport behaviour in colonies of the ant Camponotus floridanus. Our results indicate that a small number of workers, usually minors belonging to the nurse social group, are highly specialised for brood transport. There was no difference in the speed at which workers transported brood, suggesting that specialisation does not correlate with efficiency. Workers often started to transport the brood only after having identified a better location. There was no evidence that workers shared information about the presence of a better location. Notably, once brood transporters had been removed, none of the remaining workers performed this task, and the brood transport completely stopped. When brood transporters were returned to their colony, brood transport was immediately restored. Taken together, our study reveals that brood transport is an inflexible task, achieved through the synchronous actions of a few privately informed specialist workers.